Ubiquinol-cytochrome c reductase core protein 1 contributes to cardiac tolerance to acute exhaustive exercise. Issue 2 (January 2022) - Yi, Tingting; Chen, Huifang; Zhan, Jian; Li, Yu; Long, Zonghong; Wu, Zhuoxi; Yang, Mi; Peng, Taotao; Li, Hong
Ubiquinol-cytochrome c reductase core protein 1 (UQCRC1) is an indispensable component of mitochondrial complex III. It plays a key role in cardioprotection and maintaining mitochondrion function. However, the exact role of UQCRC1 in maintaining cardiac function has not been reported by in vivo models. Also, the exact biological functions of UQCRC1 are far from fully understood. UQCRC1 +/− mice had decreased both mRNA and protein expression of UQCRC1 in the left ventricular myocardia, and these mice had reduced tolerance to acute exhaustive exercise including decreased time and distance with higher apoptosis rate, higher expression level of cleaved CASPASE 3, and higher ratio of cleaved PARP1 to full-length PARP1. Moreover, UQCRC1 knockdown led to increased LV interventricular septal thicknesses both at systole and diastole, as well as decreased LV volume both at end-systole and end-diastole. Finally, UQCRC1 gene disruption resulted in mitochondrial vacuolation, fibril disarrangement, and more severe morphological and structural changes in mitochondria after acute exhaustive exercise. In conclusion, UQCRC1 contributes to cardiac tolerance to acute exhaustive exercise in mice, and it may be an essential component of complex III, playing a crucial role in maintaining cardiac functions.